Influenza vaccination coverage in Lombardy Region: a twenty-year trend analysis (1999-2019) - Rossi, Deanna; Croci, Roberto; Affanni, Paola; Odone, Anna; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2020)
Recent events and phenomena, such as A(H1N1) pandemic in 2009, “Fluad case” (2014-2015) andthe spread of vaccine hesitancy, affected influenza vaccination coverage rates in Italy. In this study, the annualcoverage rates in Lombardy Region and in Italy (from 1999-2000 season) have been critically described andcompared. Regarding both the general population and the elderly over-65s, Lombardy’s coverages alwaysremained consistently below the national average. However, declines and peaks occurred simultaneously. Thecurrent slight recovery, both at national and regional level, is not sufficient. Coverages are still widely belowthe recommended thresholds.